Nail changes in leprosy: Onychoscopy evaluation - Ruovinuo Theunuo; Sarita Sasidharanpillai; Kidangazhiathmana Ajithkumar; Biju George; Roshni S Salim (Wolters Kluwer Medknow Publications, 2020)
Context: Repeated trauma involving extremities (in the setting of peripheral neuropathy) and poor vascularity that impairs wound healing are important causes of disability and deformity in leprosy patients. Nail changes can serve as indicators of trophic changes due to leprosy. Aims: To describe the onychoscopy findings in leprosy cases and to identify any specific findings in leprosy patients in comparison to controls. Settings and Design: The first 30 leprosy patients and 30 age and sex-matched controls who attended our tertiary care center from 1 August 2018 were included in this cross-sectional study. Materials and Methods: Onychoscopy examination of all fingernails was performed at 50× magnification using dinolite dermoscope AM4113ZT under non-polarizing light to document surface changes and under polarizing light to document pigmentation and vascular changes. Statistical Analysis: The observed nail changes in cases and controls were compared using Pearson's Chi-square test. Results: Statistically significant association with leprosy was found for pitting, onycholysis, melanonychia, transverse lines, nail pallor, and onychauxis. Nail pallor was unique to leprosy patients. Limitations: Small sample size and not evaluating toenails were the major limitations of the study. Conclusions: Studies with large sample size are needed to assess the significance of nail pallor as a specific onychoscopy finding in leprosy.